PENGARUH LATIHAN LADDER DRILL TERHADAP KECEPATAN LARI 60 METER PADA SISWA SEKOLAH BOLA BASKET LOC SIDOARJO - Nuryadi, Achmad; Firmansyah, Guntur (JP.JOK (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2018)
Abstract  The research approach used is a type of experimental research using a pre-experimental design that is one group pretests-posttest design. From the data analysis above, the results obtained for the correlation of 0.877 from mean X1 = 9.9700 with a standard deviation of 0.62619 and mean X2 = 9.8108 with a standard deviation of 0.6380, while for the results of the pre-test and post-test results obtained mean 0.159220 with a standard deviation of 0.32138 and the result of the t test is 2.477, thus Ho is accepted so that the ladder drill exercise provided can increase the running speed of 60 meters in Sidoarjo LOC Basketball School.